Hydrogen Trap in Fine Ca(OH)2 Powder Made from Scallop-Shell Waste. (4th January 2017) - Tsuchida, Hirotsugu; Aramaki, Masatoshi; Furukimi, Osamu; Kato, Yoshimine
Abstract : Hydrogen trap was implied for calcium hydroxide Ca(OH)2 powder made form scallop (Patinopecten yessoensis) shell waste at high temperature of around 800°C to 900°C. Large quantities of seashells are abandoned every day and it is important to make use of them. The Ca(OH)2 powder was made by heating the fine grain scallop-shell powder up to about 1100°C and then quenched in water. Then the Ca(OH)2 powder was heated at temperature between 600 °C and 1300 °C for 30 min. in flowing Ar + 3% hydrogen gas. The hydrogen trap of the heat-treated scallop-shell powder was measured by using oxidation-reduction potential (ORP) analysis and nuclear magnetic resonance (NMR). At heat-treatment temperature of 900°C, the samples showed the lowest ORP that implies the highest adsorption of hydrogen. The NMR study also revealed an observation of sharp peaks at the 900°C, implying hydrogen trap as well.